Folk Tales From Around The World - Retold by Border, Rosemary (New York Oxford University Press, 2005)
In different places, people tell different stories. In Germany, a village is full of rats. A strange man arrives to help. In Japan, a boy draws dragons. They save his life. In Africa, a mother looks for stories. Find out where she finds them. This book contains tales from around the world.
Include Color Illustrations
Keywords: Reading (Elementary) -- Tales -- Folklore